Indonesia : Evaluation of the Urban Community Driven Development Program, Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan - World Bank (Washington, DC, 2014)
Indonesia's Program Nasional Pemberdayaan Masyarakat (PNPM) is the largest Community Driven Development (CDD) program in the world covering all urban wards (PNPM-Urban) and rural villages (PNPM-Rural) in Indonesia. This policy note summarizes a comprehensive process evaluation of the PNPM-Urban program which has been carried by the Research and Development (RAND) corporation in collaboration with survey meter, as well as a rapid appraisal of two pilot subcomponents of the PNPM-Urban program: the Neighborhood Development Scheme (ND), and Poverty Alleviation Partnership Grant Mechanism (PAPG) carried out by a small team of consultants. The RAND evaluation was designed to look at how specific aspects of the program are working, document good practice, distill lessons learned, and identify options for program reform based mainly on a qualitative field study in a sample of kelurahans. This paper is organized as follows: section one gives introduction and approach. The main findings of the evaluation and rapid appraisal are summarized in section two, followed by a discussion and recommendations for program design in section three. The full studies including detailed findings and data are available as companions to this policy note.